Evolutionary Conserved Cysteines Function as cis-Acting Regulators of Arabidopsis PIN-FORMED 2 Distribution - Retzer, Katarzyna; Lacek, Jozef; Skokan, Roman; Del Genio, Charo I; Vosolsobě, Stanislav; Laňková, Martina; Malínská, Kateřina; Konstantinova, Nataliia; Zažímalová, Eva; Napier, Richard M; Petrášek, Jan; Luschnig, Christian (International journal of molecular sciences, 2017)
Coordination of plant development requires modulation of growth responses that are under control of the phytohormone auxin. PIN-FORMED plasma membrane proteins, involved in intercellular transport of the growth regulator, are key to the transmission of such auxin signals and subject to multilevel surveillance mechanisms, including reversible post-translational modifications. Apart from well-studied PIN protein modifications, namely phosphorylation and ubiquitylation, no further post-translational modifications have been described so far. Here, we focused on root-specific Arabidopsis PIN2 and explored functional implications of two evolutionary conserved cysteines, by a combination of in silico and molecular approaches. PIN2 sequence alignments and modeling predictions indicated that both cysteines are facing the cytoplasm and therefore would be accessible to redox status-controlled modifications. Notably, mutant pin2C-A alleles retained functionality, demonstrated by their ability to almost completely rescue defects of a pin2 null allele, whereas high resolution analysis of pin2C-A localization revealed increased intracellular accumulation, and altered protein distribution within plasma membrane micro-domains. The observed effects of cysteine replacements on root growth and PIN2 localization are consistent with a model in which redox status-dependent cysteine modifications participate in the regulation of PIN2 mobility, thereby fine-tuning polar auxin transport.
Keywords: transport proteinů; protein modeling; Arabidopsis; cystein; intracellular distribution; Cysteine; plasma membrane protein sorting; kořeny rostlin; PIN proteins; Membrane Microdomains; Auxin; Protein Transport; kyseliny indoloctové; konzervovaná sekvence; Indoleacetic Acids; SRRF; protein mobility; Arabidopsis Proteins; Conserved Sequence; Plant Roots; membránové mikrodomény; root phenotype; proteiny huseníčku